Pengaruh Strategi Marketing dan Brand Image. Terhadap Volume Penjualan Obat-Obatan Vitacimin PT. Takeda Indonesia Sumatera Utara - Putra , Syah Roni; Waruwu, Khamo; Hasanah, Uswatun (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2022)
The purpose of this study was to determine the effect of marketing strategy and Brand Image. on sales volume of PT Vitacimin drugs. Takeda Indonesia, North Sumatra. This research was conducted at PT. Takeda Indonesia, North Sumatra, with a population and sample of 60 Outlines (Supermarkets, Minimarkets and Wholesalers) were taken by purposive sampling. The research instrument was a questionnaire with a Likert scale model. The requirements test is carried out by testing the validity and reliability tests as well as the classical assumption test. The data analysis technique used is multiple regression technique at a significance level of α = 0.05.The results of partial hypothesis testing have proven that there is an influence between advertising strategy on sales volume with a significant value level of 0.001 <0.05, thus Ha is accepted and Ho is rejected. The results of partial hypothesis testing have proven that the influence between Brand Image. on Sales Volume has a significant effect of 0.000 <0.05. Thus Ha is accepted H0 is rejected. Furthermore, the F test proves that the two independent variables have a simultaneous effect on the dependent variable with a significant value of 0.000 <0.05 which is stated to have a positive and significant effect.From the results of the SPSS output it is known that the R square value simultaneously gives an effect with a percentage of 53.6% and the advantage is that it is influenced by other factors which are not examined in this discussion at 46.4%.